Variations in Kiwifruit Microbiota across Cultivars and Tissues during Developmental Stages - Su-Hyeon Kim; Da-Ran Kim; Youn-Sig Kwak (The Plant Pathology Journal, 2023)
The plant microbiota plays a crucial role in promoting plant health by facilitating the nutrient acquisition, abiotic stress tolerance, biotic stress resilience, and host immune regulation. Despite decades of research efforts, the precise relationship and function between plants and microorganisms remain unclear. Kiwifruit (Actinidia spp.) is a widely cultivated horticultural crop known for its high vitamin C, potassium, and phytochemical content. In this study, we investigated the microbial communities of kiwifruit across different cultivars (cvs. Deliwoong and Sweetgold) and tissues at various developmental stages. Our results showed that the microbiota community similarity was confirmed between the cultivars using principal coordinates analysis. Network analysis using both degree and eigenvector centrality indicated similar network forms between the cultivars. Furthermore, Streptomycetaceae was identified in the endosphere of cv. Deliwoong by analyzing amplicon sequence variants corresponding to tissues with an eigenvector centrality value of 0.6 or higher. Our findings provide a foundation for maintaining kiwifruit health through the analysis of its microbial community.